THE ROLE OF THE FINANCE POWER IN THE POST-WAR RECONSTRUCTION OF UKRAINE - BAK, Nataliia (Scientific journal «World of Finance», 2023)
Introduction. Despite the active military actions, a strategy for the further development of the Ukrainian state is being formed today. The strategy requires a specification of an effective mechanism for accumulating and allocating society’s financial resources. Representatives of economic science and specialists of state authorities are working to calculate the quantitative parameters of such a financial mechanism. However, the qualitative characteristics of financial foundations for future social organization remain insufficiently transparent and understandable. Among them, the power factor plays a leading role. The purpose of the article is to substantiate the theoretical foundations of the role of finance in the post-war reconstruction of Ukraine through the prism of the functioning of the institution of power. Methods. General scientific and special methods are used: analysis, synthesis, grouping, description, theoretical generalization, and abstract-logical method. Results. As a result of the study, the necessity of identifying priorities for the development of Ukrainian society and the national economy from the standpoint of the formation and functioning of the centers of financial power is substantiated. These priorities include civil society, public administration institutions, local self-government bodies, business, as well as public and private, real and financial sectors of the economy. Balancing economic interests and capabilities of the centers of financial power requires purposeful changes in the areas of taxation and use of state financial resources, modernization of the real sector of the national economy on an innovative basis, and development of financially capable civil institutions and business communities. Conclusions. Taking into account the factor of financial power, main directions of the further development of Ukrainian society are democratization of social relations, deregulation and liberalization of economic relationships, decentralization of the process of distribution and redistribution of the GDP value, definancialization and full achievement of the goal of the fiscal decentralization policy.